Implementasi Manajemen Mutu Terpadu di Madrasah Ibtidaiyah - Rohmat Rohmat; Yuslam Yuslam (UIN Prof. K.H. Saifuddin Zuhri Purwokerto, 2022)
The quality of madrasah education is influenced by internal and external factors of madrasas. The transformation process in schools / madrasas is influenced by input and environment. Various systems in madrasas have an impact on how perceptions, understandings, consensus, and madrasa commitment to quality, both in planning, implementation, and control. Thus, it is necessary to learn more about their perceptions, understandings, and consensus on the quality of education and what the reality of the quality of madrasa education is. So that madrasas need to implement integrated quality management. This research uses qualitative research methods using research samples at MIN 1 Banyumas and MI MA Nu 1 Pageraji Banyumas. The research findings are as follows: integrated quality management principles conducted at MIN 1 Banyumas and MI Ma